Increasing age in Achilles rupture patients over time. Issue 7 (July 2017) - Ho, Gavin; Tantigate, Direk; Kirschenbaum, Josh; Greisberg, Justin K.; Vosseller, J. Turner
Abstract: Background: The changing demographics of Achilles tendon rupture (ATR) patients have not fully been investigated. However, there has been a general suspicion that this injury is occurring in an increasingly older population, in terms of mean age. The aim of this study was to objectively show an increase in age in Achilles tendon rupture patients over time. Methods: Published literature on Achilles tendon ruptures was searched for descriptive statistics on the demographics of patients in the studies, specifically mean and median age of Achilles tendon rupture patients, gender ratio, percentage of athletics-related injuries, percentage of smokers, and BMI. Linear regression analyses were performed to determine the trend of patient demographics over time. A Welch one-way ANOVA was carried out to identify any possible differences in data obtained from different types of studies. Results: The patient demographics from 142 studies were recorded, with all ATR injuries occurring between the years 1953 and 2014. There was no significant difference in the mean age data reported by varying study types, i.e. randomized controlled trial, cohort study, case series, etc. ( P  = 0.182). There was a statistically significant rise in mean age of ATR patients over time ( P <  0.0005). There was also a statistically significant drop in percentage of male ATR patients ( P  = 0.02). There is no significant trend for percentage of athletics-related injuries, smoking or BMI. Conclusion: Since 1953 to present day, the mean age at which ATR occurs has been increasing by at least 0.721 years every five years. In the same time period, the percentage of female study patients with ATR injuries has also been increasing by at least 0.6% every five years. Level of evidence: Level III; Retrospective cohort study